The Genetic Estimation of Fruit Component Parameters of Seven Coconut Populations Without a Progeny Test - Dwi Asmono; Alex Hartana; Edi Guhardja; Sudirman Yahya (Forum Pasca Sarjana, 1993)
Heritability of fruit characters, such as fruit weight, husk weight, husk thickness, sheal weight, endosperm (water) weight, albumen weight, copra weight, oil content, fruit length and ftuit width. have been estimated on seven coconut populations. The results showed that most of the fruit components of Malayan Red Dwarf (MRD) and Malayan Yellow Dwarf (Mm)had relatively high heritability (>0.80), except fruit weight of MRD (0.74) and albumen weight of MYD (0.78). On the other hand, the heritability of those characters in tall populatidns varied between population. All of fruit characters on Polynesian Tall (PYT) and Seruwai Tall (SAT) had relatively high heritability (>0.80). On West African Tall (WAT), most Of the heritability of the fruit characters were relatively high (>0.80). except husk weight (0.75). endosperm weight (0.79) and oil content (0.41). Heritability of seven characters of Bali Tall (BLT) were relatively high, but those of three characters were relatively low; i.e. husk weight (0.52). fruit width (0.56) and husk thickness (0.71). Three fruit characters of Rmnell Tall (RLT) shown higher heritability. those are husk thickness (0.87), endosperm weight (0.92) and fruit length (0.90).